DIRECTION OF PROFESSIONAL TRAINING AS A RISK FACTOR OF INVOLVEMENT OF YOUTH IN ASOCIAL GROUPS - T. Banshchikova (Вестник Северо-Кавказского федерального университета)
The article describes the results of a study of the latent and obvious riskiness of socio-psychological conditions that form the psychological readiness for addictive behavior of student youth. The study involved 2 463 respondents aged 17-25 years. It has been established: young people of socionomic professions are more susceptible to the influence of the group than others, they are inclined to risk (danger), they are more anxious, impulsive, more often than others experience a state of frustration and are ready to accept asocial attitudes of society. Protection factors are most pronounced among respondents of techno-economic (engineering) professions. These indicators make it possible to increase the socio-psychological resistance to the effects of risk factors.